Designing a CIP system - Ahmad, Arshad (Faculty of Chemical & Natural Resources Engineering, 1991)
Safety and quality are the two important keywords in food manufacturing. A lot of efforts are being carried out to achieve them. Modifications and improvements are being made in many aspects in order to stay competitive in the current market. One important factor in achieving these objectives, which unfortunately being overlooked is hygienic design. Safety and product quality are actually built in the design of the plant itself. This paper illustrates an aspect in hygienic plant design - Cleaning In Place (CIP).